The 100 Most-Cited Articles in the Field of Colorectal Diseases from 1955 to 2020: A Bibliometric Analysis - Zhang, Chunmei; Luo, Mengqi; Zhu, Hanlong; Zhou, Jian; Miao, Lin (Turkish Journal of Gastroenterology, 2022)
Background: The number of times that an article is cited could reflect its impact. This study aims to recognize and analyze the characteristics of the most frequently cited articles in the field of colorectal diseases. Methods: We identified the 100 most-cited articles using the terms “colorectal,” “colon,” “rectal,” “IBD,” “ulcerative colitis,” “Crohn’s disease,” or “colonoscopy” in Web of Science. The articles were analyzed to evaluate the characteristics, including the number of citations, country of origin, the institution of origin based on the first author’s affiliation, study type, and others. Results: Of the top-cited publications, the number of citations ranged from 1575 to 9283, with a mean of 2504.11 citations. The journal with the greatest number of most-cited articles was the New England Journal of Medicine (n = 23), followed by Science (n = 14) and Nature (n = 12). These papers were published in 14 different countries, of which more than half were from the United States (n = 60). The most popular field was colorectal cancer (n = 45), followed by colon tumors (n = 21). Most of the papers were basic science studies (n = 43) and randomized controlled trials (n = 30). Regarding the level of evidence, there were 5 studies at level I, 29 at level II, and 5, 1, and 15 studies at levels III, IV, and V, respectively. Conclusion: Our study could provide a historical perspective on scientific progress in the field of colorectal diseases. These 100 mostcited articles are of great significance for helping researchers understand this field over time.